Chemical composition, antimicrobial and larvicidal activities of essential oils of two Syzygium species from Vietnam - L. T. Huong; B. B. Thinh; N. H. Hung; H. V. Phu; N. C. Hieu; D. N. Dai (Brazilian Journal of Biology, 2023)
Abstract The present study is the first to investigate the chemical composition, antimicrobial and larvicidal activities of the essential oils from the leaves of Syzygium attopeuense (Gagnep.) Merr. & L.M.Perry and Syzygium tonkinense (Gagnep.) Merr. & L.M.Perry collected in Vietnam. The essential oils were extracted by hydrodistillation and analyzed by GC and GC–MS. The study indicated the presence of a high percentage of sesquiterpenes in both investigated essential oils. The major components of S. attopeuense essential oil were bicyclogermacrene (24.26%), (E)-caryophyllene (11.72%), and (E)-β-ocimene (6.75%), whereas S. tonkinense essential oil was dominated by (E)-caryophyllene (80.80%). The antimicrobial activity of essential oils was evaluated by broth microdilution assay to determine the minimum inhibitory concentration (MIC) and median inhibitory concentration (IC50). Both essential oils exhibited remarkable inhibitory activity against all tested Gram-positive bacteria and yeast than Gram-negative bacteria. Among them, essential oils of S. attopeuense and S. tonkinense possessed the strongest activity against Enterococcus faecalis (MIC = 4.00 μg/mL; IC50 = 1.69 μg/mL) and Candida albicans (MIC = 16.00 μg/mL; IC50 = 8.67 μg/mL), respectively. Furthermore, the larvicidal activity of essential oils was tested using fourth-instar larvae of Aedes aegypti. Results from the larvicidal test revealed that both essential oils had an excellent inhibitory effect against A. aegypti larvae with LC50 values from 25.55 to 30.18 μg/mL and LC90 values from 33.00 to 39.01 μg/mL. Our findings demonstrate that the essential oil extracted from S. attopeuense and S. tonkinense are potential sources of natural antimicrobials and can act as inexpensive mosquito larvicidal agents.